STUDENTS' CRITICAL THINKING OF HEAT AND MATTER - Yustika Syabandari (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2019)
Modern technologies have shaped human lives but technologies that facilitate rapid information sharing can enable misleading information. Thus, it becomes pertinent that man should think critically when presented with daily problems information. This study explored students’ critical thinking when presented with daily problems con-cerning heat and matter, which are prone to misunderstanding. Results suggested that students are moderately critical when presented with daily problems concerning heat and matter. The correlation between each critical thinking element is also discussed.